Prenatal Care Disruptions and Associations With Maternal Mental Health During the COVID-19 Pandemic - Groulx, Taylor; Bagshawe, Mercedes; Giesbrecht, Gerald; Tomfohr-Madsen, Lianne; Hetherington, Erin; Lebel, Catherine A. (Frontiers in Global Women's Health, 2021)
As the novel coronavirus (COVID-19) spread across Canada in March 2020, provinces imposed restrictions. These changes impacted how pregnant individuals received prenatal care and experienced childbirth. The stress caused by these changes may negatively affect the well-being of pregnant individuals with impacts on the developing child. This study investigated the impact of the pandemic on prenatal care and birth plans of pregnant individuals in Canada and potential associations with maternal mental health. Data from 4,604 participants was collected from English- and French-speaking Canadians between April 5 and June 1, 2020 as part of the Canada-wide Pregnancy During the COVID-19 Pandemic study. Symptoms of maternal depression, general anxiety, and pregnancy-related anxiety were assessed. Participants also answered questions about disruptions and changes to prenatal care and their birth plans due to the COVID-19 pandemic. Logistic regression was used to estimate associations between prenatal care disruptions and maternal mental health. Cancellation of prenatal appointments and birth plan changes (specifically changes to childcare during birth and change of support person attending the birth) were significantly associated with greater odds of experiencing clinically elevated depression, anxiety, and/or pregnancy-related anxiety symptoms. These results highlight the need for reliable and accessible prenatal care during the pandemic, such as the integration of mental health screenings and co-ordination of prenatal care providers.